HUMBERT HUMBERT’S DEFENSE MECHANISM IN VLADIMIR NABAKOV’S LOLITA - DUWI WAHYU UTAMI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2013)
Abstrak Penelitian ini berfokus pada menggambarkan mekanisme pertahanan yang dilakukan oleh tokoh utama dan mengapa karakter utama menggunakan mekanisme pertahanan. Mekanisme pertahanan yang digunakan sebagai akibat dari kegagalannya kehilangan orang yang dicintai. Masalah pertama berbicara tentang mekanisme pertahanan Humbert Humbert. Masalah kedua mengungkapkan alasan Humbert Humbert menggunakan mekanisme pertahanan. Untuk menjawab masalah pertama, penelitian ini menggunakan teori mekanisme pertahanan oleh Sigmund Freud dan didukung oleh buku Albertine Minderop. Masalah kedua dijawab dengan menggunakan konsep trauma, stres dan kecemasan. Data ini menyajikan mekanisme pertahanan Humbert Humbert dan alasannya menggunakan mekanisme pertahanan. Analisis mengungkapkan sembilan jenis mekanisme pertahanan Humbert Humbert. Mereka adalah Displacement, Intelektualisasi, Rasionalisasi, pembentukan Reaksi, Represi, Denial, Sublimasi, dan Bertindak keluar. Mekanisme pertahanan ini yang digunakan untuk mengurangi kecemasan Humbert Humbert terhadap kenangan masa lalunya dalam kegiatan sehari-hari. Selain itu, mekanisme pertahanannya juga muncul sebagai akibat dari kegagalan masa kecilnya ketika ia kehilangan orang yang dia cintai sebelumnya. Selain itu, ada beberapa alasan yang membuat Humbert Humbert menggunakan mekanisme pertahanan. Yaitu trauma, stres dan kecemasan akan diungkapkan sebagai penyebab Humbert Humbert melakukan mekanisme pertahanan. Kata kunci : Mekanisme pertahanan, trauma, stres dan kecemasan Abstract This study focuses on depicting defense mechanism performed by the main character and why the main character uses the defense mechanism. The defense mechanism is used as the result of his failure losing a beloved one. The first problem talks about Humbert Humbert’s defense mechanism. The second problem reveals Humbert Humbert’s reason of using defense mechanism. To answer the first problem, this study uses the theory of defense mechanism by Sigmund Freud’s and supported by Albertine Minderop’s book. The second problem is answered by using the concept of  trauma, stress and anxiety. The data presents Humbert Humbert’s defense mechanism and the reason of using defense mechanism. The analysis reveals Humbert Humbert’s nine types of defense mechanism. They are Displacement, Intellectualization, Rationalization, Reaction formation, Repression, Denial, Sublimation, and Acting out. Those defense mechanisms are used to reduce Humbert Humbert’s anxiety toward his past memory in his daily activities. Besides, his defense mechanism also emerges as a result of his failure of his childhood when he lost whom he loved before. Besides, there are some reasons  that make Humbert Humbert use defense mechanism. They are trauma, stress and anxiety will reveal as the causes of Humbert Humbert use defense mechanism. Keywords : Defense mechanism, trauma, stress and anxiety